PELATIHAN PENGGUNAAN APLIKASI MICROSOFT EXCEL UNTUK PEMBELAJARAN PERSAMAAN AKUNTANSI - Suwandi, Suwandi; Turini, Turini; Akbari, Safitri; Nurhana Dhea Praadha Gitama, Gytha; Kartika, Ika (Universitas Islam Malang, 2025)
Accounting learning at the secondary school level often faces obstacles in conveying basic concepts, especially in understanding the accounting equation. Students often experience difficulties in recording and processing financial transactions systematically due to the limitations of manual learning methods. To overcome this problem, Lecturers at Catur Insan Cendekia University (UCIC) Cirebon held Community Service activities in the form of training on the use of the Microsoft Excel application as a tool in learning accounting equations at Putera Nirmala High School - Cirebon City. This activity aims to improve students' understanding and skills in utilizing Microsoft Excel to compile and analyze financial transactions more effectively and efficiently. The implementation method uses a service learning (SL) approach, which includes material presentation, demonstration of relevant Excel features, and hands-on practice with accounting equation case studies. The results of the activity showed a significant increase in participants' ability to apply Microsoft Excel to prepare simple financial reports. With this training, it is hoped that accounting learning in high school can be more interactive, innovative and in line with developments in digital technology.